TINDAK TUTUR DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS X DI MA UNGGULAN AL-KAUTSAR TROWULAN MOJOKERTO TAHUN PELAJARAN 2015/2016 - Malutin Malutin; Suyadi Suyadi; Doni Uji Windiatmoko (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2018)
This research is about speech acts in learning Indonesian class X students in MA Unggulan Al-kautsar Trowulan Mojokerto 2015/2016 lesson year. This study aims to (1) describe how the speech acts of introgative conversations of teachers and students of class X in MA Unggulan Al-kautsar Trowulan Mojokerto 2015/2016 lesson year, (2) describe how the speech declarative speech conversation of teachers and students of class X in the Supreme Court of Al -kautsar Trowulan Mojokerto academic year 2015/2016. (3) describe how the speech speech imperative speech of teachers and students of class X in MA Supreme Al-kautsar Trowulan Mojokerto academic year 2015/2016.This study used descriptive qualitative method. The object of research in the form of speech and the end result of research in the form of description. Data collection techniques used in the study are data reduction, data presentation, and withdrawal of results obtained.The results of the analysis of research data can be concluded tuturan conducted teachers and students have many functions of language such as speech acts conversation function when answering a question. This research is expected to provide benefits for teachers as educators in communicating and for learners can be used to improve in ethics talk with others. Keywords: Speech, Function, Language Learning